2020
DOI: 10.1016/j.ejso.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Refined TNM-staging for pancreatic adenocarcinoma – Real progress or much ado about nothing?

Abstract: In order to provide optimal cancer care and prognostication, it is necessary to stage the disease. The 8th edition of the TNM-staging for exocrine pancreatic ductal adenocarcinoma (PDAC) system has refined size-based T-stages and number-based N-categories. However, several impediments to the value of this may exist. For one, even at small size (e.g. <0.5 cm), PDACs readily metastasize, making size unreliable to predict behavior. The increasing shift towards neoadjuvant treatments for both resectable and border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…These small studies showed that the mechanisms underlying lymph node invasion may have effects on the survival rate, however, the data are contradictory [ 7 , 8 , 9 , 10 , 11 , 12 ]. In addition, the latest TNM classification—the 8th edition of the American Joint Committee on Cancer (AJCC) with changes to the T and N categories—does not consider the mechanisms of lymph node involvement [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These small studies showed that the mechanisms underlying lymph node invasion may have effects on the survival rate, however, the data are contradictory [ 7 , 8 , 9 , 10 , 11 , 12 ]. In addition, the latest TNM classification—the 8th edition of the American Joint Committee on Cancer (AJCC) with changes to the T and N categories—does not consider the mechanisms of lymph node involvement [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with pancreatic cancer, the disease staging and surgical resectability criteria were applied by The American Joint Committee on Cancer (AJCC) cancer staging manual 8th edition and TNM staging [19].…”
Section: Eus-fna or Eus-fnb And Cyto/histopathological Evaluationmentioning
confidence: 99%
“…The increasing shift towards neoadjuvant treatments for both resectable and borderline PDAC, and the use of conversion therapy for locally advanced disease suggest the need for biological predictors in addition to the UICC TNM stage [19]. As these predictors are not currently clinically employed, we focused on the ability of the combination of PODXL and ITGB1 to predict the postoperative prognosis of PDAC patients with UICC TNM stage IA-IIA,…”
Section: Ability Of the Combination Of Podxl And Itgb1 To Predict The...mentioning
confidence: 99%